Formulasi dan Karakterisasi Edible Film dari Poliblen Pati Umbi Talas Kimpul – Polivinil Alkohol dengan Polietilen Glikol sebagai Plasticizer - Dedi Nofiandi; Yahdian Rasyadi; Muthia Miranda Zaunit; Mellani Pratiwi (JURNAL KATALISATOR, 2021)
This research was conducted to develop the utilization of starch from talas kimpul (Xanthosoma sagittifolium), which is currently only used as a food ingedidient. In this study, an edible film was made by varying the starch of talas kimpul with Polyvinyl Alcohol (PVA) in order to obtain an edible film that met the requirements. Edible film was made with a ratio of talas kimpul starch-PVA, namely F1 (1:1), F2 (1:2) and F3 (2:1) with a total of 6 grams of polyblend in 100 ml, the plasticizer used was poly ethylene glycol (PEG) as much as 30% of the total polyglene. The edible film was prepared using the solvent casting method with the principle of gelatinization. The edible film obtained were characterized: organoleptic, thickness, pH, moisture content, absorption profile, percent elongation, tensile strength, Young’s modulus, and water vapor transmission rate. The results indicated that all formulas meet the requirements as edible film.